Plasma trough concentrations of darunavir/ritonavir and raltegravir in older patients with HIV‐1 infection. Issue 7 (24th January 2017) - Calza, L; Colangeli, V; Magistrelli, E; Bussini, L; Conti, M; Ramazzotti, E; Mancini, R; Viale, P
Abstract : Objectives: The aim of the study was to assess plasma concentrations of darunavir/ritonavir and raltegravir in older patients compared with younger patients with HIV‐1 infection. Methods: In this observational, open‐label study, adult HIV‐infected out‐patients aged ≤ 40 years (younger patients) or ≥ 60 years (older patients) and treated with tenofovir/emtricitabine plus darunavir/ritonavir (800/100 mg daily) or raltegravir (400 mg twice daily) were asked to participate. The trough concentrations ( C trough ) of darunavir/ritonavir and raltegravir were assessed at steady state using a validated high‐performance liquid chromatography (HPLC)−tandem mass spectrometry method. Results: A total of 88 HIV‐positive patients were enrolled in the study. Forty‐six patients were treated with darunavir/ritonavir, and 42 with raltegravir. The geometric mean plasma C trough (coefficient of variation) of raltegravir was comparable between the 19 older and 23 younger subjects: 106 ng/mL (151%) and 94 ng/mL (129%), respectively [geometric mean ratio (GMR) 0.85; 95% confidence interval (CI) 0.71–1.57; P = 0.087]. In contrast, the geometric mean plasma C trough of darunavir was significantly higher among the 21 older patients [2209 ng/mL (139%)] than among the 25 younger patients [1876 ng/mL (162%); GMR 1.56; 95% CI: 1.22–1.88; P = 0.004]. Similarly, the geometric mean C trough of ritonavir was significantly higher among older than among younger individuals. Conclusions: The mean plasma C trough of darunavir and ritonavir was significantly higher in older patients than in younger patients with HIV‐1 infection, while the mean plasma level of raltegravir was comparable in the two groups. However, both regimens showed good tolerability in both younger and older subjects.